Improving Table Tennis Learning in Physical Education Through Theory and Practice - Andika Bayu, I Made; Husni Fahritsani; Agung Mahendra (Universitas PGRI Palembang, 2025)
This research aims to develop and test eligibility material teach e-modul eye studying theory and practice of table tennis learning. Method study used namely research And development ( research and development ) from theory Borg And Gall Which own 10 stages development. Stages started from; (1) research and information collection, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing (validation The product is carried out by involving expert judgment, namely material experts, media experts and experts learning ), (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation . However, due to time and cost constraints, this study only goes as far as at the 4th stage, namely preliminary field testing . Data collection using observation, questionnaire, And interview. Technique analysis data Which used in study This is descriptive qualitative statistics . The product produced is in the form of an e-module for theoretical courses. and table tennis learning practices. Based on the feasibility test of the development product e-learning materials The theoretical and practical course module for learning table tennis, obtained the results of the assessment by media experts with a very valid and usable category, while the results of the material expert assessment were obtained results with category valid And can used with revision, And results evaluation expert learning obtained results with category valid And can used with revision. Based on the results of the feasibility test for the development of e-module teaching materials for theory and practice courses table tennis learning practice, obtained the percentage results of the feasibility assessment scores from the test subjects try student program studies education physical University Indonesian Teachers Association Palembang that is as big as 61% with the category “Worthy/Attractive/Good”. Thus the results of the development of the e-module for the subject studying theory And practice learning table tennis worthy For used as material teach student.